Integrated inferences : causal models for qualitative and mixed-method research - Humphreys, Macartan; Jacobs, Alan M. (Alan Michael) (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
'Introduces a Bayesian approach to the use of causal models to design and carry out qualitative and mixed-methods research. Addressed to researchers across the social sciences, this book shows how causal models allow us to combine extensive and intensive data strategies to answer both general and case-specific causal questions'--
Includes bibliographical references and index.
Keywords: Qualitative research -- Methodology; Mixed methods research; Social sciences -- Methodology; Social sciences -- Research -- Mathematical models